Efficacy and safety of a new pneumatic compression device for peripheral arterial disease with intermittent claudication - Breu, F. X.; Zelikovski, A.; Loberman, Z.; Rauh, G. (Phlebologie, 2014)
Background: The primary objective of the study was to demonstrate that Intermittent Pneumatic Compression (IPC) with the new ANGIO PRESS™ IPC device can significantly improve the walking distance, i.e. pain free initial intermittent claudication distance (ICD) and the absolute claudication distance (ACD) in patients with stage II peripheral arterial occlusive disease (PAD) compared to control treatment.Patients and methods: A total of 67 patients were screened and randomized into the study in four clinical centers based in Israel and Germany. Patients were randomized to one of the two study groups: 1. Medication treatment with ASS / Clopidogrel and standardized walking exercise with additional IPC treatment, two times per day for 1.5 hours for three months. 2. Medication treatment and standardized walking exercise alone. The safety and efficacy of the ANGIO PRESS™ device was determined for the treatment of symptoms of PAD Fontaine stage IIb by measuring the pain free walking distance, the absolute walking distance, the ankle-brachial-index (ABI) and the walking pain. Additionally the quality of life (QOL) of each subject was assessed according to the SF-36 questionnaire. Subjects were followed up at six weeks and 3 months.Results: No statistical differences were observed in any of the demographic characteristics and baseline scores. A significant difference was found between the treatment and control group in the ACD and the walking pain scale. Subjects in the treatment group improved their total walking distance in 54 meters, an improvement of 40% compared to their baseline distance. The walking pain improved by 1.89 points in the treatment group. Despite the fact that the difference in the ICD between the study groups were not found significantly different, the mean change from baseline in ICD score at the three month visit in the treatment group of 37 m was found statistically significant (p=0.0002), whereas the mean change of 20.7 m in the control group was not found significantly different. No changes were found between the study groups in the ABI and the QOL. The treatment was easy to tolerate and most patients suffered no side-effects, nor complained of any significant discomfort. Two subjects suffered from SAEs which were determined as not related to the study treatment.Conclusion: The ANGIO PRESS™ is a non-invasive, easy to use, home treatment which is safe and moderately effective for the treatment of intermittent claudication. The ability of subjects to improve their absolute walking distance and reduce the walking pain on the same time may offer a significant value for patients at early stages of PAD who are not indicated for an invasive treatment.
Keywords: Intermittent Pneumatic Compression; IPC; Peripheral Arterial Disease; intermittent claudication; walking exercise